THU0570 A Pilot Evaluation of Arthritis Self-Management Program by Lay Leaders in Patients with Chronic Inflammatory Arthritis in Hong Kong. (10th June 2014) - Leung, Y.Y.; Kwan, J.; Chan, P.; Tam, L.S.; Li, E.K.; Kwok, A.
Abstract : Background: Healthcare system has been shifting towards a partnership model of care. Objectives: To evaluate the 6-week community based lay-led Arthritis Self-Management Program (ASMP) among patients with chronic inflammatory arthritis in Hong Kong, and evaluate the effectiveness of "shared care collaboration" between hospital care and community organizations. Methods: A total of 17 lay leaders with chronic inflammatory arthritis were trained. Patients with chronic inflammatory arthritis were recruited via newly established referral systems from hospital rheumatology centers to community. Participants were allocated to experimental group or a wait list control group. Evaluation questionnaires were completed before, after (6 week) and 3 months after ASMP. We performed analysis of covariance for significant difference in various outcomes after ASMP, all analysis adjusted for age, sex, marital status, education, employment, duration of illness and disability at baseline. Results: A total of 88 female and 9 male participants with ankylosing spondylitis (6.2%), psoriatic arthritis (13.4%) and rheumatoid arthritis (80.4%) were recruited. Referrals were from hospital rheumatology centers, community organizations and patient self-help groups in 26.4%, 54.7%, and 12.6% respectively. The mean (SD) age and duration of illness were 52.0 (11.4) and 5.6 (7.3). A total of 65 and 32 participants completed evaluation in the experimental group and control group. At the end of 6 weeks, the experimental group had significantly less pain (p=0.049), used more cognitive methods to manage symptoms (p=0.01) and practiced more aerobic exercise (p=0.049) after adjustment of covariance. The experimental group had a trend of improvement in self-efficacy, fatigue, self-rated health status, health distress, role limitation, disability and health related quality of life. At 3 months, the frequencies of stretching and aerobic exercise were increased in the experimental group. Conclusions: In this pilot study, the lay led ASMP conducted in community base showed positive beneficial effects on participants with chronic inflammatory arthritis. Significant improvement in pain, cognitive management and frequencies of exercise was observed. Shared care collaboration between physicians, community organizations and patient self-help group was demonstrated. Acknowledgements: This project is supported by the Hong Kong Arthritis Foundation Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.1647